Ideology as Performance in The Power of the Powerless. Issue 2 (May 2018) - Danaher, David S.
While ideology is a central concept in Václav Havel's master essay, at no point does he operate with a standard definition of the term. Instead, Havel "defines" ideology in metaphorical and performative terms, reframing our understanding of its meaning and power in the modern world by focusing on its pre-political operation. This point has yet to be appreciated by scholars of Havel. To better understand the import of Havel's approach, this essay details metaphorical contexts for ideology in The Power of the Powerless and draws connections to ideological performativity in Havel's plays from the 1970s as well as in the cinema of the Czech New Wave.